A web-based system for localization data presentation - Siak, Huey Xhin. (2013)
With the advancement in technology, researches have been done in areas such as Wi-Fi Positioning Systems (WPS). Mall operators could make use of this technology to track the behaviours of customers in a shopping mall. The client and server architecture could be implemented. In this case a web based platform was created to act as the client and the EasyPHP software as the server.